Keeping Cell Death in Check: Ubiquitylation-Dependent Control of TNFR1 and TLR Signaling - Griewahn, Laura; Köser, Aaron; Maurer, Ulrich (Frontiers in Cell and Developmental Biology, 2019)
Pro-inflammatory signaling, induced by pathogens, tissue damage or cytokines, depends on the ubiquitylation of various subunits of receptor signaling complexes, which are controlled by ubiquitin ligases and deubiquitinases. Ubiquitylation sets the stage for the activation of kinases within these complexes, which ultimately regulate pro-inflammatory gene expression. The receptors, which transduce pro-inflammatory signals, can often induce cell death, which is regulated by polyubiquitylation as well. In this review, we discuss the key role of ubiquitylation in pro-inflammmatory signaling by TNF and TLRs and its role in setting the threshold for cell death induced by these pro-inflammatory triggers.